Analisis Faktor-Faktor Kesulitan Belajar Bahasa Arab Siswa Kelas Vii Madrasah Tsanawiyah Nurul Hikmah Gantar Indramayu - Supanto, Supanto; Fanirin, Moch Hasyim; Arifin, Moh Mas'ud (Lembaga Penelitian dan Pendidikan Mandala, 2023)
Based on observations in several Madrasah Ibtidaiayah and Madrasah Tsanawiyah neighborhoods in the areas of Mekarsari, Haukolot and Gantar, many students when asked Arabic they looked embarrassed and could not answer from this problem which motivated the author to raise the title related to